Coherent coupling between distant excitons revealed by two-dimensional nonlinear hyperspectral imaging - Kasprzak, J; Patton, B; Savona, V; Langbein, W (2011)
Coherent coupling between distant two-level systems is a fundamental process in several physical contexts, from natural photosynthesis to quantum-information processing, where it enables two-qubit operations. For quantum information, qubits based on electronic degrees of freedom in a solid-state matrix are sensible candidates for scalable, integrated implementations. Clarifying the mechanisms underlying coherent coupling in solids is therefore an essential step in the development of such technology. Here, we demonstrate the existence of a long-range coherent coupling mechanism between individual localized excitons in a 5a nm GaAs/AlGaAs quantum well, introducing the novel tool of two-dimensional nonlinear coherent hyperspectral imaging. The coupling is shown to arise due to a biexcitonic renormalization, rather than a transition dipole (Förster) interaction. The long-range nature of the coupling is attributed to the existence of spatially extended exciton states up to the micrometre range, which are admixed in the biexciton state, as revealed in nonlinear imaging. © 2011 Macmillan Publishers Limited. All rights reserved.